Policies to restrict unhealthy food and beverage advertising in outdoor spaces and on publicly owned assets: A scoping review of the literature. (16th November 2021) - Chung, Alexandra; Zorbas, Christina; Riesenberg, Devorah; Sartori, Ainslie; Kennington, Kelly; Ananthapavan, Jaithri; Backholer, Kathryn
Summary: Unhealthy food marketing influences attitudes, preferences, and consumption of unhealthy foods, leading to excess weight gain. Outdoor advertising is highly visible (often displayed on publicly owned assets), but the evidence supporting regulation is unclear. This systematic scoping review of academic and grey literature aimed to (1) describe potential health and economic impacts of implementing government‐led policies that restrict unhealthy food advertising in outdoor spaces or on public assets (including studies examining prevalence of advertising, associations with health outcomes and interventional studies); (2) identify and describe existing policies; and (3) identify factors perceived to have influenced policy implementation. Thirty‐six academic studies were eligible for inclusion. Most reported on prevalence of unhealthy food advertising, demonstrating high prevalence around schools and in areas of lower socioeconomic position. None examined health and economic impacts of implemented policies. Four jurisdictions were identified with existing regulations; five had broader marketing or consumer protection policies that captured outdoor food marketing. Facilitators of policy implementation included collaboration, effective partnerships, and strong political leadership. Barriers included lobbying by food, media, and advertising industries. Implementation of food marketing policies in outdoor spaces and on public assets is feasible and warranted. Strong coalitions and leadership will be important to drive the policy agenda forward.